Anthralin modulates the expression pattern of cytokeratins and antimicrobial peptides by psoriatic keratinocytes. Issue 3 (September 2017) - Holstein, Julia; Fehrenbacher, Birgit; Brück, Jürgen; Müller-Hermelink, Eva; Schäfer, Iris; Carevic, Melanie; Schittek, Birgit; Schaller, Martin; Ghoreschi, Kamran; Eberle, Franziska C.
Highlights: Anthralin directly induces cell apoptosis in keratinocytes in vitro, but not in 3D psoriasis tissue models. Keratinocyte proliferation as determined by Ki-67 staining is impaired by anthralin in vivo . Anthralin rapidly normalizes cytokeratin 16 expression in lesional skin but not in 3D psoriasis tissue models. DEFB4A expression is suppressed by anthralin in vitro and in vivo . Abstract: Background: Psoriasis is an inflammatory skin disease with aberrant keratinocyte proliferation, presumably as a result of immune cell activation. Th17 cytokines like IL-17A and IL-22 are critically implicated in epidermal thickening, altered keratinocyte differentiation and production of innate factors such as antimicrobial peptides. Psoriasis treatment options include modern targeted therapies using anti-cytokine antibodies and traditional non-targeted treatments like anthralin (dithranol). While the mode of action of anti-cytokine antibodies is defined, the effects of topical anthralin on psoriatic skin are not fully understood. Objective: This study aims to unravel the direct effects of anthralin on keratinocyte proliferation, differentiation and production of psoriasis-associated factors. Methods: We tested the effects of anthralin on cell proliferation, cytokeratin expression and changes in the expression of antimicrobial peptides using primary keratinocytes and 3D psoriasis tissue models with and without stimulation of the psoriasis-promoting cytokines IL-17A and IL-22. Moreover, we compared the findings derived from monolayer and multilayer cultures to data derived from lesional skin of patients with psoriasis before and under treatment with anthralin. Results: Our study shows that anthralin directly induces cell apoptosis in vitro in monolayer cultures but not in 3D psoriasis tissue models treated with IL-17A and IL-22. Yet, keratinocyte proliferation as determined by Ki-67 staining is impaired by anthralin in vivo . In lesional skin but not in 3D psoriasis tissue models anthralin rapidly normalizes cytokeratin (CK)16 expression. Furthermore, anthralin directly inhibits DEFB4 expression in vitro and in vivo, while other antimicrobial peptides and cytokines studied like IL-6 and IL-8 are regulated differently in vitro and in vivo . Conclusions: Our results show that anthralin directly regulates DEFB4A expression. However, its beneficial effects on psoriasis cannot be explained by direct effects on keratinocyte differentiation or cytokine expression.